UCLA METHOD: THE CHARACTER EDUCATION EVALUATION ON BASIC MATHEMATICS LEARNING IN HIGHER EDUCATION - Martyana Prihaswati; Eko Andy Purnomo; Sukestiyarno -; Mulyono - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The external turmoil that occurs today has a negative impact on all the structure and order of the domestic system. One of the recovery efforts is the implementation of mental revolution through character education. The character education can be applied to the affective aspect ofthe basic mathematics learning which will be integrated with basic mathematics material using character to be implemented. In addition, the colleges can be a place for student character development. This research was conducted at Muhammadiyah University of Semarang andSemarang State University. This research is a quantitative descriptive research using UCLA evaluation method. The data were collected by questionnaire method and interview. The results showed, 1) lecturers have little impact on the development of student character.2) program planning, given the integrated learning character education. 3) Program implementation, character education has never been introduced or used in the majority of learning. Indirectly, some character education indicators have been embedded in the students.However, most indicators are still not fully embedded, such as honesty, religious, caring for others, discipline, hard work, self-reliance, and responsibility. Thus, it is necessary to develop character values on basic mathematics learning applied to processes, techniques, andassessment instruments.Keywords: Character education, UCLA, basic